Ultrahigh-strength steel, preparation method thereof, electronic equipment structural member and electronic equipment
Ultra-high-strength steel is prepared by mixing alloy powder and binder and heat treatment methods, which solves the problems of difficult processing and insufficient performance of ultra-high-strength steel, and achieves the improvement of high yield strength, tensile strength and elongation. It is suitable for Electronic equipment structural parts extend the service life of the equipment.
Patent Information
- Application Number
- CN202310731897.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-17
- Publication Date
- 2024-12-17
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Ultra-high-strength steel has problems such as high hardness, difficult processing and further improvement in performance during processing and use.
After mixing alloy powder with binder, granulation, injection molding, degreasing and sintering, combined with heat treatment, ultra-high strength steel containing Ni, Co, Mo and other elements is prepared to form excellent yield strength and tensile resistance. Materials of strength and plasticity.
It realizes the high yield strength, tensile strength and elongation of ultra-high strength steel, reduces processing difficulty, improves the comprehensive performance of the material, is suitable for electronic equipment structural parts, and extends the service life of the equipment.
Smart Images

Figure CN119144910A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of electronic products, and specifically relates to ultra-high strength steel and a preparation method thereof, electronic equipment structural parts and electronic equipment. Background Art
[0002] With the continuous development of electronic equipment, the materials used for electronic equipment structural parts are becoming more and more abundant. Steel has become one of the most used materials in the world due to its low price and reliable performance. Ultra-high strength steel refers to steel with a yield strength greater than 1180MPa and a tensile strength greater than 1380MPa. It is widely used due to its excellent strength. However, ultra-high strength steel is relatively hard and difficult to process, which limits the use of ultra-high strength steel. At the same time, the performance of ultra-high strength steel needs to be further improved. Summary of the invention
[0003] In view of this, the present application provides ultra-high strength steel and a method for preparing the same, an electronic equipment structural component and an electronic equipment.
[0004] In a first aspect, the present application provides an ultra-high strength steel, the chemical composition of which includes 16wt% to 20wt% Ni, 13wt% to 17.5wt% Co, 5.5wt% to 8.5wt% Mo, less than or equal to 1wt% Cr, less than 2wt% V, less than or equal to 0.35wt% O, less than or equal to 0.15wt% C, and the balance Fe.
[0005] In a second aspect, the present application provides a method for preparing ultra-high strength steel, comprising: mixing an alloy powder with a binder, and then granulating the mixture to obtain a feed; injecting, degreasing and sintering the feed to obtain a prefabricated material; and heat treating the prefabricated material to obtain an ultra-high strength steel, wherein the chemical composition of the ultra-high strength steel includes 16wt% to 20wt% Ni, 13wt% to 17.5wt% Co, 5.5wt% to 8.5wt% Mo, less than or equal to 1wt% Cr, less than 2wt% V, less than or equal to 0.35wt% O, less than or equal to 0.15wt% C, and the remainder Fe.
[0006] In a third aspect, the present application provides an electronic equipment structural component, wherein the material of the electronic equipment structural component includes the ultra-high strength steel described in the first aspect or the ultra-high strength steel produced by the preparation method described in the second aspect.
[0007] In a fourth aspect, the present application provides an electronic device, comprising the electronic device structure described in the third aspect.
[0008] The ultra-high strength steel provided by the present application combines high strength with good plasticity, has excellent comprehensive performance, and is conducive to the processing and use of ultra-high strength steel; the preparation method of the ultra-high strength steel is simple, and the ultra-high strength steel of the desired shape can be directly obtained by the preparation method, which can reduce the processing flow and is conducive to its use. The electronic equipment structural parts with the ultra-high strength steel have excellent performance, can increase the service life of the electronic equipment, and are conducive to the use of the electronic equipment. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] In order to more clearly illustrate the technical solutions in the implementation modes of the present application, the drawings required for use in the implementation modes of the present application will be described below.
[0010] Figure 1 A flow chart of a method for preparing ultra-high strength steel provided in one embodiment of the present application.
[0011] Figure 2 A flow chart of a method for preparing ultra-high strength steel provided in another embodiment of the present application.
[0012] Figure 3 A flow chart of a method for preparing a structural component of an electronic device provided in one embodiment of the present application.
[0013] Figure 4 A front view of an electronic device provided in accordance with an embodiment of the present application.
[0014] Figure 5 This is a metallographic image of the prefabricated material obtained after sintering in Example 1.
[0015] Figure 6 This is a schematic diagram of the electronic device structure prepared in Example 1.
[0016] Figure 7 This is the metallographic image of the prefabricated material obtained after sintering in Example 2. DETAILED DESCRIPTION
[0017] The following are exemplary implementations of the present application. It should be noted that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present application, and these improvements and modifications are also considered to be within the scope of protection of the present application.
[0018] The disclosure below provides many different embodiments or examples to realize the technical solution of the present application. In order to simplify the disclosure of the present application, the setting of specific examples is described below. Of course, they are only examples, and the purpose is not to limit the present application. In addition, the present application can repeat reference numbers and / or reference letters in different examples, and this repetition is for the purpose of simplification and clarity, and itself does not indicate the relationship between the various embodiments and / or settings discussed. In addition, the examples of various specific processes and materials provided in the present application, but those of ordinary skill in the art can be aware of the application of other processes and / or the use of other materials.
[0019] The present application provides an ultra-high strength steel, the chemical composition of which includes 16wt% to 20wt% Ni, 13wt% to 17.5wt% Co, 5.5wt% to 8.5wt% Mo, less than or equal to 1wt% Cr, less than 2wt% V, less than or equal to 0.35wt% O, less than or equal to 0.15wt% C, and the balance Fe. The ultra-high strength steel provided by the present application has high yield strength and tensile strength, and suitable elongation and elastic modulus, so that the ultra-high strength steel has excellent strength and plasticity, excellent comprehensive performance, and is conducive to the use of ultra-high strength steel. It can be understood that wt% is weight percentage, that is, by weight percentage, the chemical composition of the ultra-high strength steel includes 16% to 20% Ni, 13% to 17.5% Co, 5.5% to 8.5% Mo, less than or equal to 1% Cr, less than 2% V, less than or equal to 0.35% O, less than or equal to 0.15% C and the balance Fe.
[0020] In the present application, nickel (Ni) is an austenite-forming element, which makes it easier for steel to obtain single-phase austenite when heated, so that lath martensite can be obtained when cooled. Ni can also reduce the starting temperature of martensitic phase transformation, so that martensite is easier to obtain when cooled, and it helps to increase the content of residual austenite and improve plasticity. At the same time, Ni can inhibit the decomposition of screw dislocations in the structure of martensitic aging steel to ensure that cross-slip can be carried out. Whether the material can cross-slip is a sign of its plasticity and toughness. Ni is an element that contributes to plasticity and toughness in ultra-high strength steel; Ni can also promote precipitation strengthening and improve the strength of ultra-high strength steel. Among them, austenite is a solid solution formed by carbon dissolving in γ-Fe, and martensite is a supersaturated solid solution of carbon in α-Fe, which is formed by austenite through diffusionless phase transformation. In the present application, the ultra-high strength steel contains 16wt% to 20wt% Ni. If the Ni content is too low, it is difficult to form a single austenite, which reduces the content of residual austenite in the ultra-high strength steel, and is not conducive to the improvement of the ductility of the ultra-high strength steel; if the Ni content is too high, it is not conducive to the formation of martensite, and will increase the content of residual austenite in the ultra-high strength steel, which is not conducive to the improvement of the strength of the ultra-high strength steel; therefore, the use of 16wt% to 20wt% Ni not only ensures the improvement of the strength of the ultra-high strength steel, but also avoids the reduction of the plasticity of the ultra-high strength steel, which is conducive to obtaining ultra-high strength steel with excellent comprehensive properties. Specifically, the content of Ni in the ultra-high strength steel may be, but is not limited to, 16wt%, 16.3wt%, 16.6wt%, 16.9wt%, 17wt%, 17.2wt%, 17.5wt%, 17.7wt%, 18wt%, 18.5wt%, 18.8wt%, 19wt%, 19.3wt%, 19.7wt% or 20wt%, etc. Exemplarily, the content of Ni in the ultra-high strength steel may be 16wt% to 18wt%, 16.3wt% to 18wt%, 17wt% to 18wt%, 17.5wt% to 19.1wt%, 17.5wt% to 20wt%, 18wt% to 19.2wt% or 18.5wt% to 20wt%, etc.
[0021] In one embodiment of the present application, the content of Ni in the ultra-high strength steel is 16wt% to 18wt%, which is conducive to further improving the rigidity of the ultra-high strength steel. Specifically, the content of Ni in the ultra-high strength steel may be, but is not limited to, 16.1wt% to 16.8wt%, 16.3wt% to 17.2wt%, 16.5wt% to 17.9wt%, 16.8wt% to 18wt%, 17wt% to 18wt%, 17.1wt% to 17.9wt% or 17.2wt% to 17.8wt%, etc.
[0022] In the present application, the cobalt element (Co) can promote the complete transformation of austenite into martensite, increase the starting temperature of martensite transformation, and reduce the tendency of martensite to transform into reverse transformation austenite; Co is only dissolved in the martensite matrix and does not form intermetallic compounds. It mainly affects the dislocation substructure and provides a uniform nucleation position for the precipitation phase. Co reduces the solubility of Mo, thereby promoting the precipitation and uniform distribution of Mo-containing intermetallic compounds. Therefore, the combination of Co and Mo produces a strengthening effect and improves the strength of ultra-high strength steel; Co can also increase the dislocation density, prevent dislocations from recovering during tempering, and improve the strength of ultra-high strength steel. In the present application, the use of 13wt% to 17.5wt% Co ensures the improvement of the strength of ultra-high strength steel, which is conducive to obtaining ultra-high strength steel with excellent yield strength and tensile strength. Specifically, the content of Co in the ultra-high strength steel may be, but is not limited to, 13wt%, 13.3wt%, 13.5wt%, 13.9wt%, 14wt%, 14.2wt%, 14.5wt%, 14.8wt%, 15wt%, 15.3wt%, 15.5wt%, 15.8wt%, 16wt%, 16.4wt%, 16.7wt%, 17wt%, 17.2wt%, or 17.5wt%, etc. Exemplarily, the content of Co in the ultra-high strength steel may be 13.3wt% to 17.5wt%, 13.5wt% to 17.5wt%, 14wt% to 17wt%, 14.5wt% to 17.2wt%, 14.8wt% to 17wt%, 15wt% to 17.5wt%, or 16wt% to 17.5wt%, etc.
[0023] In one embodiment of the present application, the content of Co in the ultra-high strength steel is 13.5wt% to 17.5wt%, which is conducive to further improving the yield strength and tensile strength of the ultra-high strength steel, so that the ultra-high strength steel has excellent strength and is more conducive to its use. Specifically, the content of Co in the ultra-high strength steel can be, but is not limited to, 13.5wt% to 17wt%, 13.8wt% to 17.1wt%, 14.2wt% to 16.9wt%, 14.5wt% to 16.5wt%, 15wt% to 17wt% or 15wt% to 16.5wt%, etc.
[0024] In the present application, molybdenum (Mo) is the main strengthening element, which produces solid solution strengthening and improves the comprehensive performance of strength and plastic toughness of ultra-high strength steel; Mo can reduce the starting temperature of martensitic phase transformation, promote the precipitation of intermetallic compounds and the formation of precipitation phase, and promote the strengthening phase not to precipitate in a grid shape along the original austenite grain boundary, so that it cannot be segregated at the grain boundary, and improve fracture toughness. In the present application, the use of 5.5wt% to 8.5wt% of Mo not only ensures the improvement of the strength of ultra-high strength steel, but also ensures the improvement of the plasticity of ultra-high strength steel. Specifically, the content of Mo in ultra-high strength steel can be but not limited to 5.5wt%, 5.6wt%, 5.9wt%, 6wt%, 6.1wt%, 6.3wt%, 6.5wt%, 6.8wt%, 7wt%, 7.2wt%, 7.5wt%, 7.7wt%, 8wt%, 8.3wt% or 8.5wt%, etc. For example, the content of Mo in the ultra-high strength steel may be 5.5wt% to 8wt%, 5wt% to 8.5wt%, 5.8wt% to 7.9wt%, 6wt% to 7.5wt%, or 6wt% to 8.3wt%, etc.
[0025] In one embodiment of the present application, the content of Mo in the ultra-high strength steel is 6wt% to 7.4wt%, which is beneficial to further improve the elongation of the ultra-high strength steel, improve the comprehensive performance of the ultra-high strength steel, and is more conducive to the use of the ultra-high strength steel. Specifically, the content of Mo in the ultra-high strength steel can be, but is not limited to, 6wt%, 6.1wt%, 6.2wt%, 6.3wt%, 6.4wt%, 6.5wt%, 6.6wt%, 6.7wt%, 6.8wt%, 7wt%, 7.2wt%, 7.3wt% or 7.4wt%, etc.
[0026] In the present application, iron (Fe) is used as a basic element of ultra-high strength steel to ensure the basic performance of ultra-high strength steel. Specifically, the content of Fe in ultra-high strength steel may be, but is not limited to, greater than or equal to 52wt%, greater than or equal to 54wt%, greater than or equal to 55wt%, greater than or equal to 58wt%, greater than or equal to 59.5wt%, greater than or equal to 60wt%, greater than or equal to 62wt%, greater than or equal to 63wt%, greater than or equal to 65wt%, etc. In one embodiment of the present application, the content of Fe in ultra-high strength steel may be 52wt% to 60wt%.
[0027] In the present application, the content of chromium (Cr) in the ultra-high strength steel is less than or equal to 1wt%. That is, the ultra-high strength steel provided in the present application is a system with Ni, Co, and Mo as the main elements. By controlling the content of Cr, an adverse effect on the strength of the ultra-high strength steel is avoided. Specifically, the content of Cr in the ultra-high strength steel may be, but is not limited to, less than or equal to 0.2wt%, less than or equal to 0.3wt%, less than or equal to 0.5wt%, less than or equal to 0.6wt%, less than or equal to 0.7wt%, less than or equal to 0.8wt%, or less than or equal to 0.83wt%, etc.
[0028] In the present application, the content of vanadium (V) in the ultra-high strength steel is less than or equal to 2wt%. By controlling the content of V, it is beneficial to ensure the toughness of the ultra-high strength steel. Specifically, the content of V in the ultra-high strength steel may be, but is not limited to, less than or equal to 0.6wt%, less than or equal to 0.8wt%, less than or equal to 1wt%, less than or equal to 1.2wt%, less than or equal to 1.5wt%, or less than or equal to 1.7wt%, etc.
[0029] In the present application, the content of oxygen element (O) in the ultra-high strength steel is less than or equal to 0.35wt%. By controlling the content of O, the increase of hot brittleness of the ultra-high strength steel is avoided. Specifically, the content of O in the ultra-high strength steel may be, but is not limited to, less than or equal to 0.25wt%, less than or equal to 0.28wt%, less than or equal to 0.3wt%, less than or equal to 0.31wt%, less than or equal to 0.33wt%, or less than or equal to 0.34wt%, etc.
[0030] In the present application, the content of carbon element (C) in the ultra-high strength steel is less than or equal to 0.15wt%. That is, the ultra-high strength steel provided in the present application is a low carbon steel. By controlling the content of C, the influence on the performance of the ultra-high strength steel can be avoided. Specifically, the content of C in the ultra-high strength steel may be, but is not limited to, less than or equal to 0.03wt%, less than or equal to 0.05wt%, less than or equal to 0.07wt%, less than or equal to 0.08wt%, less than or equal to 0.1wt%, less than or equal to 0.12wt% or less than or equal to 0.13wt%, etc.
[0031] In the present application, the ultra-high strength steel contains inevitable impurity elements. In one embodiment of the present application, the content of impurity elements in the ultra-high strength steel is less than or equal to 0.5wt%. By controlling the content of impurity elements, the influence on the performance of ultra-high strength steel is avoided, which is beneficial to the use of ultra-high strength steel. Specifically, the content of impurity elements in ultra-high strength steel may be, but is not limited to, less than or equal to 0.2wt%, less than or equal to 0.25wt%, less than or equal to 0.3wt%, less than or equal to 0.35wt%, less than or equal to 0.4wt% or less than or equal to 0.43wt%, etc.
[0032] In one embodiment of the present application, the impurity elements include at least one of sulfur (S), silicon (Si), manganese (Mn), phosphorus (P), titanium (Ti) and aluminum (Al). In one embodiment of the present application, the content of S in the ultra-high strength steel is less than or equal to 0.02wt%. Too much S will affect the thermoplasticity and toughness of the ultra-high strength steel. By controlling the content of S to be less than or equal to 0.02wt%, the performance of the ultra-high strength steel can be guaranteed. Specifically, the content of S in the ultra-high strength steel may be, but is not limited to, less than or equal to 0.001wt%, less than or equal to 0.005wt%, less than or equal to 0.008wt%, less than or equal to 0.01wt%, less than or equal to 0.015wt% or less than or equal to 0.018wt%, etc. In one embodiment of the present application, the content of Si in the ultra-high strength steel is less than or equal to 0.2wt%, thereby avoiding the precipitation of harmful phases and improving the performance of the ultra-high strength steel. Specifically, the content of Si in the ultra-high strength steel may be, but is not limited to, less than or equal to 0.11wt%, less than or equal to 0.13wt%, less than or equal to 0.15wt%, less than or equal to 0.16wt%, or less than or equal to 0.18wt%, etc. In one embodiment of the present application, the content of Mn in the ultra-high strength steel is less than or equal to 0.1wt%, which is beneficial to improving the corrosion resistance of the ultra-high strength steel. Specifically, the content of Mn in the ultra-high strength steel may be, but is not limited to, less than or equal to 0.02wt%, less than or equal to 0.05wt%, less than or equal to 0.06wt%, less than or equal to 0.07wt%, or less than or equal to 0.08wt%, etc. In one embodiment of the present application, the content of P in the ultra-high strength steel is less than or equal to 0.01wt%, so as to avoid increasing the brittleness of the ultra-high strength steel. Specifically, the content of P in the ultra-high strength steel may be, but is not limited to, less than or equal to 0.002wt%, less than or equal to 0.005wt%, less than or equal to 0.007wt%, less than or equal to 0.008wt%, or less than or equal to 0.009wt%, etc. In one embodiment of the present application, the content of Ti in the ultra-high strength steel is less than or equal to 0.01wt%, so as to avoid affecting the toughness of the ultra-high strength steel. Specifically, the content of Ti in the ultra-high strength steel is less than or equal to 0.003wt%, less than or equal to 0.005wt%, less than or equal to 0.006wt%, less than or equal to 0.008wt%, or less than or equal to 0.009wt%, etc. In one embodiment of the present application, the content of Al in the ultra-high strength steel is less than or equal to 0.01wt%. Al is easy to form brittle inclusions in steel and affect toughness, and the Al content is controlled to ensure the toughness of the ultra-high strength steel. Specifically, the content of Al in the ultra-high strength steel is less than or equal to 0.001wt%, less than or equal to 0.003wt%, less than or equal to 0.005wt%, less than or equal to 0.007wt% or less than or equal to 0.008wt%, etc. In one embodiment, the ultra-high strength steel does not contain Al.
[0033] In one embodiment of the present application, the chemical composition of the ultra-high strength steel includes Ni, Co, Mo, impurity elements and Fe. In one embodiment of the present application, the chemical composition of the ultra-high strength steel also includes at least one of Cr, V, O and C. In another embodiment of the present application, the ultra-high strength steel consists of Ni, Co, Mo, impurity elements, Fe, and at least one of Cr, V, O and C.
[0034] In the present application, the ultra-high strength steel is a martensitic aging steel, which is based on carbon-free or micro-carbon martensite and can produce ultra-high strength steel that is precipitated and hardened by intermetallic compounds during aging, relying on the dispersion precipitation strengthening of intermetallic compounds. In one embodiment of the present application, the mass content of martensite in the ultra-high strength steel is greater than or equal to 85%. That is to say, in the production process of ultra-high strength steel, firstly, by solid solution, the impurity elements or precipitated phases in the sintered material are completely dissolved in the ferrite to finally form full austenite, and then by rapid cooling to below the end point of the martensitic transformation temperature, the austenite is transformed into full martensite, and after deep cooling, the precipitation of the precipitated phase is controlled by aging treatment to achieve a significant increase in strength. Specifically, the mass content of martensite in ultra-high strength steel can be, but is not limited to, more than 85%, more than 86%, more than 88%, more than 90%, more than 92%, more than 93% or more than 95%, etc. In one embodiment of the present application, the ultra-high strength steel also has residual austenite, and the residual austenite in the ultra-high strength steel has a certain effect on the improvement of plasticity. In one embodiment of the present application, the ultra-high strength steel also has reverse transformation austenite. In one embodiment of the present application, the ultra-high strength steel also has a dispersed phase. The dispersed phase is an intermetallic compound, and the intermetallic compound achieves the effect of dispersion strengthening by precipitating and uniformly distributing in the ultra-high strength steel. Specifically, the dispersed phase can be, but is not limited to, intermetallic compounds of molybdenum, titanium and nickel.
[0035] In one embodiment of the present application, the yield strength of the ultra-high strength steel is greater than or equal to 2000MPa, the tensile strength is greater than or equal to 2100MPa, the elongation is greater than or equal to 3%, and the elastic modulus is greater than or equal to 170Gpa. Yield strength is the yield limit of ultra-high strength steel when yielding occurs, that is, the stress that resists micro plastic deformation; tensile strength is the critical value of the transition of ultra-high strength steel from uniform plastic deformation to local concentrated plastic deformation, and it is also the maximum bearing capacity of ultra-high strength steel under static tensile conditions; elongation is an indicator that describes the plastic properties of ultra-high strength steel, and the elastic modulus is a measure of the ability to resist elastic deformation; according to GB / T 228.1-2021, the yield strength, tensile strength, elongation and elastic modulus are tested. The ultra-high strength steel provided in this application has excellent yield strength and tensile strength, while maintaining a high elongation and elastic modulus, and has excellent performance, which is conducive to the use of ultra-high strength steel. Specifically, the yield strength of ultra-high-strength steel may be, but is not limited to, 2000 MPa or more, 2050 MPa or more, 2080 MPa or more, 2100 MPa or more, 2150 MPa or more, 2190 MPa or more, 2200 MPa or more, or 2240 MPa or more; the tensile strength of ultra-high-strength steel may be, but is not limited to, 2100 MPa or more, 2150 MPa or more, 2200 MPa or more, 2250 MPa or more, 2300 MPa or more, 2350 MPa or more, 2400 MPa or more, or 2450 MPa or more; the elongation of ultra-high-strength steel may be, but is not limited to, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, or more. In one embodiment of the present application, the yield strength of the ultra-high strength steel is 2000MPa to 2250MPa, the tensile strength is 2100MPa to 2450MPa, the elongation is 3% to 6%, and the elastic modulus is 170Gpa to 195Gpa. The ultra-high strength steel has excellent comprehensive performance, which is conducive to its use in electronic equipment. In another embodiment of the present application, the yield strength of the ultra-high strength steel is 2100MPa to 2250MPa, the tensile strength is 2200MPa to 2450MPa, the elongation is 4% to 6%, and the elastic modulus is 180Gpa to 195Gpa.
[0036] The present application also provides a method for preparing ultra-high strength steel, which can prepare the ultra-high strength steel in any of the above embodiments. Figure 1 , is a flow chart of a method for preparing ultra-high strength steel provided in one embodiment of the present application, comprising:
[0037] S101: After the alloy powder is mixed with the binder, it is granulated by internal mixing to obtain feed.
[0038] S102: The feed material is injected, degreased and sintered to obtain a prefabricated material.
[0039] S103: The prefabricated material is heat treated to obtain ultra-high strength steel.
[0040] In the related art, the preparation of ultra-high strength steel requires smelting, and the production conditions are relatively harsh, and the equipment requirements are high. At the same time, due to the high strength of ultra-high strength steel, the processing and molding process is difficult, which is not conducive to its use. The present application adopts the method of alloy powder injection (MIM) molding to obtain prefabricated materials, and then obtains ultra-high strengthening steel through heat treatment; the preparation method is simple and easy to operate. In actual production, the ultra-high strength steel of the desired shape can be obtained by controlling the shape of the mold during injection, eliminating the processing of ultra-high strength steel materials (such as CNC, etc.), reducing the preparation cost and difficulty of use. At the same time, the preparation method can be used to obtain ultra-high strength steel with excellent comprehensive performance, which is conducive to its use in electronic equipment, especially as a structural part of precise size and shape or a structural part of small size and shape. Therefore, the ultra-high strength steel of the present application is made by MIM molding process.
[0041] In S101, the alloy powder is mixed with the binder, and the mixture is granulated to obtain a feed for injection. In one embodiment of the present application, the binder includes 3wt% to 5wt% (such as 3wt%, 3.2wt%, 3.5wt%, 4wt%, 4.5wt%, 4.7wt% or 5wt%) of polyethylene, 2wt% to 6wt% (such as 2wt%, 2.5wt%, 3wt%, 4wt%, 5wt%, 5.5wt% or 6wt%) of vinyl acetate polymer and the remainder of polyoxymethylene. Polyoxymethylene can be decomposed into water and gas under the action of nitric acid, and has a good removal effect. By adding polyethylene to adjust the content of polyoxymethylene in the binder, the vinyl acetate polymer plays the role of a binder, and the polyethylene and vinyl acetate polymer can be removed during the sintering process to avoid carbon residue. Specifically, the content of polyethylene in the binder may be, but is not limited to, 3wt% to 4wt%, 3.3wt% to 4.5wt%, 3.8wt% to 4wt%, 4wt% to 5wt% or 4.1wt% to 4.9wt%, etc., and the content of vinyl acetate polymer may be, but is not limited to, 2wt% to 5wt%, 2.1wt% to 4.4wt%, 2.2wt% to 3.8wt%, 2.5wt% to 5.4wt%, 3wt% to 5wt% or 4wt% to 5.5wt%, etc. Further, the binder may also include 1wt% to 3wt% (such as 1wt%, 1.5wt%, 2wt%, 2.5wt% or 3wt%) of antioxidant to avoid the influence of oxygen during the preparation process. In one embodiment of the present application, the binder is obtained by mixing polyoxymethylene, polyethylene and vinyl acetate polymer at 150° C. to 170° C. (such as 150° C., 155° C., 160° C., 165° C. or 170° C., etc.) for 60 min to 120 min (such as 60 min, 70 min, 80 min, 90 min, 100 min, 110 min or 120 min, etc.). In one embodiment, the components of the binder can be mixed in a kneader according to the proportions to obtain the binder.
[0042] In one embodiment of the present application, the volume ratio of the alloy powder to the binder during mixing is 0.61:1 to 0.73:1, so that both the injection feeding can be obtained and the compactness after sintering can be ensured, which is conducive to obtaining high-strength materials. Specifically, the volume ratio of the alloy powder to the binder during mixing can be, but not limited to, 0.61:1, 0.63:1, 0.64:1, 0.65:1, 0.68:1, 0.7:1 or 0.72:1, etc. In one embodiment of the present application, in the mixture formed by the alloy powder and the binder, the volume ratio of the alloy powder is 58% to 62% (such as 58%, 59%, 60%, 61% or 62%), and the volume ratio of the binder is 38% to 42% (such as 38%, 39%, 40%, 41% or 42%). Specifically, in the mixture formed by alloy powder and binder, the volume proportion of alloy powder can be but not limited to 58% to 61.8%, 58.2% to 59.8%, 58.5% to 61.3%, 59% to 59.9%, 60.1% to 61.5%, 60.8% to 61.9%, etc., and the volume proportion of binder can be but not limited to 38.1% to 39.2%, 38.5% to 39.9%, 40.1% to 41%, 38.7% to 41.5%, 40.2% to 41.8%, 38.2% to 42%, etc.
[0043] In the present application, the banburying granulation can be, but is not limited to, carried out in a banbury mixer. In one embodiment of the present application, the banburying granulation includes processing at 150°C to 160°C for 90min to 120min. Specifically, the temperature of the banburying granulation can be, but is not limited to, 150°C, 152°C, 154°C, 155°C, 156°C, 157°C, 158°C or 160°C, etc., and the time of the banburying granulation can be, but is not limited to, 90min, 95min, 100min, 105min, 110min, 115min or 120min, etc. In one embodiment, the melt index of the feed can be 900g / 10min to 1600g / 10min to ensure its fluidity and facilitate injection.
[0044] In S102, the feed material can be molded into the shape of the desired structural part through injection molding, so that the desired shape can be obtained while producing ultra-high strength steel, avoiding subsequent processing, reducing the difficulty of application, and being more conducive to the preparation and use of products with precise dimensions and shapes.
[0045] In one embodiment of the present application, the injection temperature is 150°C to 250°C (such as 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C or 250°C, etc.), the injection pressure is 80MPa to 150MPa (such as 80MPa, 90MPa, 100MPa, 110MPa, 120MPa, 130MPa, 140MPa or 150MPa, etc.), and the mold cavity temperature is 100°C to 140°C (such as 100°C, 110°C, 120°C, 130°C or 140°C, etc.).
[0046] In the present application, polyformaldehyde is removed by degreasing. In one embodiment of the present application, degreasing includes heating to 110°C to 125°C (such as 110°C, 112°C, 115°C, 120°C, 123°C, 124°C or 125°C, etc.) in nitric acid and an inert gas and keeping warm for 8h to 12h (such as 9h, 10h, 11h or 12h, etc.). By using a nitric acid atmosphere, it reacts with polyformaldehyde to remove the polyformaldehyde in the binder. The reaction products are gas and water, which will not remain in the material, and nitric acid is volatile and will not remain in the material; an inert gas is introduced to prevent the influence of oxygen on the alloy powder. Among them, the inert gas can be but is not limited to nitrogen.
[0047] In the present application, decarburization is performed by sintering to obtain a high-density prefabricated material, and austenite is generated and transformed into martensite. During the martensite phase transformation, a large number of high-density dislocations gathered increase the difficulty of dislocation movement and play a strengthening role. In one embodiment of the present application, sintering includes a first stage and a second stage, the first stage includes keeping warm at 350°C to 610°C (such as 360°C, 390°C, 400°C, 450°C, 500°C, 550°C or 600°C, etc.) for 4h to 8h (such as 5h, 6h or 7h, etc.), and the second stage includes keeping warm at 1140°C to 1385°C (such as 1150°C, 1170°C, 1200°C, 1250°C, 1350°C or 1370°C, etc.) for 8h to 18h. Decarburization in the first stage is conducive to completely removing the residual binder and avoiding its influence on the material properties; the density is improved during the heat preservation process in the second stage, which is conducive to the improvement of strength, and austenite is produced at the same time, which is conducive to the subsequent acquisition of martensite. The cooling process after the second stage converts austenite into martensite. The heat preservation temperature and time in the second stage are conducive to the improvement of density and the formation of austenite. The cooling speed is conducive to the transformation of more austenite to martensite, which is conducive to the improvement of material strength and plasticity. In one embodiment of the present application, after the second stage, the temperature is cooled at a cooling rate of 35℃ / min to 45℃ / min (such as 36℃ / min, 37℃ / min, 38℃ / min, 39℃ / min, 40℃ / min, 41℃ / min, 42℃ / min, 43℃ / min or 44℃ / min, etc.), so as to ensure the transformation of austenite to martensite and improve the performance of the prefabricated material. Specifically, the cooling can be nitrogen cooling. In one embodiment of the present application, the density of the alloy powder is greater than 8.1g / cm 3 , the density of the prefabricated material is greater than 8g / cm 3 ; Through degreasing and sintering, the binder is removed, and at the same time the density does not change too much, ensuring the performance of ultra-high strength steel.
[0048] In one embodiment of the present application, the first stage includes a first sub-degreasing stage, a second sub-degreasing stage and a third sub-degreasing stage. The temperature of the first sub-degreasing stage is 350°C to 400°C (such as 360°C, 370°C, 380°C or 390°C, etc.), the temperature of the second sub-degreasing stage is 450°C to 500°C (such as 460°C, 470°C, 480°C or 490°C, etc.), and the temperature of the third sub-degreasing stage is 580°C to 610°C (such as 590°C, 595°C, 600°C or 605°C, etc.). In one embodiment, the insulation time of the first sub-degreasing stage can be 20min to 40min (such as 25min, 30min, 35min or 37min, etc.). In one embodiment, the insulation time of the second sub-degreasing stage can be 100min to 150min (such as 105min, 110min, 120min, 130min or 140min, etc.). In one embodiment, the holding time of the third sub-degreasing stage can be 100min to 150min (such as 110min, 120min, 130min or 140min, etc.). In one embodiment, the temperature is raised to the first sub-degreasing stage at a heating rate of 2°C / min to 5°C / min (such as 2.5°C / min, 3°C / min, 3.5°C / min or 4°C / min, etc.). In one embodiment, the temperature is raised from the first sub-degreasing stage to the second sub-degreasing stage at a heating rate of 1°C / min to 3°C / min (such as 1°C / min, 1.5°C / min, 2°C / min or 2.5°C / min, etc.). In one embodiment, the temperature is raised from the second sub-degreasing stage to the third sub-degreasing stage at a heating rate of 1°C / min to 3°C / min (such as 1°C / min, 1.5°C / min, 2°C / min or 2.5°C / min, etc.). In one embodiment, the first stage includes heating to 350°C to 400°C at a heating rate of 2°C / min to 5°C / min and keeping warm for 20min to 40min, then heating to 450°C to 500°C at a heating rate of 1°C / min to 3°C / min and keeping warm for 100min to 150min, and then heating to 580°C to 610°C at a heating rate of 1°C / min to 3°C / min and keeping warm for 100min to 150min. In one embodiment of the present application, the first stage is carried out under negative pressure, and the negative pressure of the negative pressure is less than 5kPa, which is more conducive to decarburization.
[0049] In one embodiment of the present application, the second stage includes a first sub-sintering stage, a second sub-sintering stage, a third sub-sintering stage and a fourth sub-sintering stage. The temperature of the first sub-sintering stage is 900°C to 950°C (such as 910°C, 920°C, 930°C or 940°C, etc.), the temperature of the second sub-sintering stage is 1130°C to 1160°C (such as 1140°C, 1145°C, 1150°C or 1155°C, etc.), the temperature of the third sub-sintering stage is 1230°C to 1260°C (such as 1240°C, 1245°C, 1250°C or 1255°C, etc.), and the temperature of the fourth sub-sintering stage is 1350°C to 1390°C (such as 1360°C, 1370°C, 1380°C or 1385°C, etc.). In one embodiment, the holding time of the first sub-sintering stage can be 50min to 70min (such as 55min, 58min, 60min or 65min, etc.). In one embodiment, the holding time of the second sub-sintering stage can be 200min to 250min (such as 210min, 220min, 230min or 240min, etc.). In one embodiment, the holding time of the third sub-sintering stage can be 200min to 250min (such as 210min, 220min, 230min or 240min, etc.). In one embodiment, the holding time of the fourth sub-sintering stage can be 200min to 250min (such as 210min, 220min, 230min or 240min, etc.). The above temperature and holding time ensure the compactness of the prefabricated material after the second stage. In one embodiment, the temperature is increased to the first sub-sintering stage at a heating rate of 2°C / min to 3°C / min (such as 2.2°C / min, 2.5°C / min, 2.7°C / min or 2.9°C / min, etc.). In one embodiment, the temperature is increased from the first sub-sintering stage to the second sub-sintering stage at a heating rate of 3°C / min to 5°C / min (such as 3.5°C / min, 4°C / min, 4.5°C / min or 4.8°C / min, etc.). In one embodiment, the temperature is increased from the second sub-sintering stage to the third sub-sintering stage at a heating rate of 0.8°C / min to 1.2°C / min (such as 0.85°C / min, 0.87°C / min, 0.9°C / min, 0.95°C / min or 1°C / min, etc.). In one embodiment, the temperature is increased from the third sub-sintering stage to the fourth sub-sintering stage at a heating rate of 0.8°C / min to 1.2°C / min (such as 0.85°C / min, 0.87°C / min, 0.9°C / min, 0.95°C / min or 1°C / min, etc.) The above-mentioned slow heating rate avoids the appearance of closed pores, which is beneficial to improving the compactness of the prefabricated material and enhancing the performance of the ultra-high strength steel.In one embodiment, the second stage includes heating from the first stage to 900°C to 950°C at a heating rate of 2°C / min to 3°C / min and keeping warm for 50min to 70min, then heating to 1130°C to 1160°C at a heating rate of 3°C / min to 5°C / min and keeping warm for 200min to 250min, then heating to 1230°C to 1260°C at a heating rate of 0.8°C / min to 1.2°C / min and keeping warm for 200min to 250min, and finally heating to 1350°C to 1390°C at a heating rate of 0.8°C / min to 1.2°C / min and keeping warm for 200min to 250min. In one embodiment of the present application, under negative pressure, the negative pressure of the negative pressure can be less than 5kPa from the first stage to the first sub-sintering stage. In another embodiment of the present application, the pressure is adjusted to 10kPa to 30kPa after heating to the first sub-sintering stage. That is, the first sub-sintering stage, the second sub-sintering stage, the third sub-sintering stage, and the fourth sub-sintering stage are performed under a pressure of 10 kPa to 30 kPa.
[0050] In S103, ultra-high strength steel with excellent performance is obtained by heat treatment. In one embodiment of the present application, the heat treatment includes solution treatment, cryogenic treatment and aging treatment in sequence. Through solution treatment, the alloy elements are dissolved in the matrix phase to form a solid solution, which plays a strengthening role; through cryogenic treatment, the content of residual austenite is minimized to improve the strength of the material; through aging treatment, a large amount of dispersed intermetallic compounds are precipitated in the supersaturated solid solution, and the intermetallic compounds hinder the movement of dislocations, play a strengthening role, significantly improve the strength but with a small loss of toughness and plasticity.
[0051] In one embodiment of the present application, the solution treatment includes treating at 940°C to 970°C for 45min to 70min. The solution treatment can have the effect of grain refinement and further enhance the strengthening effect. Specifically, the solution temperature can be but not limited to 945°C, 950°C, 955°C, 960°C, 965°C or 970°C, and the solution treatment time can be but not limited to 50min, 55min, 60min, 65min or 70min. In one embodiment of the present application, the solution treatment adopts a staged temperature increase, which can make the solution treatment more stable, the solution effect is better, and it is more conducive to the precipitation of dispersed phases in the subsequent aging process. In one embodiment, the solution treatment includes a first solution stage, a second solution stage and a third solution stage, the temperature of the first solution stage is 180°C to 220°C (such as 185°C, 190°C, 200°C, 205°C or 210°C, etc.), the temperature of the second solution stage is 580°C to 620°C (such as 585°C, 590°C, 600°C, 610°C or 615°C, etc.), and the temperature of the third solution stage is 940°C to 970°C (such as 945°C, 950°C, 960°C, 965°C or 970°C, etc.). In one embodiment, the holding time of the first solution stage is 20min to 45min (such as 25min, 30min, 35min or 40min, etc.). In one embodiment, the holding time of the second solution stage is 15min to 30min (such as 20min, 23min, 25min or 29min, etc.). In one embodiment, the holding time of the third solid solution stage is 45min to 70min (such as 50min, 55min, 60min or 65min, etc.). The temperature and holding time of the above-mentioned solid solution stage are more conducive to the solid solution of alloy elements, which helps to improve the performance of ultra-high strength steel. In one embodiment, the temperature is increased to the first solid solution stage at a heating rate of 4°C / min to 7°C / min (such as 4.5°C / min, 5°C / min, 5.5°C / min or 6°C / min, etc.). In one embodiment, the temperature is increased from the first solid solution stage to the second solid solution stage at a heating rate of 8°C / min to 12°C / min (such as 8.5°C / min, 9°C / min, 10°C / min or 11°C / min, etc.). In one embodiment, the temperature is increased from the second solid solution stage to the third solid solution stage at a heating rate of 10°C / min to 15°C / min (such as 11°C / min, 12°C / min, 13°C / min or 14°C / min, etc.). In one embodiment, the solution treatment includes heating to 180°C to 220°C at a heating rate of 4°C / min to 7°C / min and keeping warm for 20min to 45min, then heating to 580°C to 620°C at a heating rate of 8°C / min to 12°C / min and keeping warm for 15min to 30min, and then heating to 940°C to 970°C at a heating rate of 10°C / min to 15°C / min and keeping warm for 45min to 70min.In one embodiment, the solution treatment is performed in a vacuum environment, so as to avoid the influence of oxygen on the material. In one embodiment, the pressure of the first solution stage is less than -0.1 kPa, the pressure of the second solution stage is less than 0.1 kPa, and the pressure of the third solution stage is less than 0.1 kPa. Specifically, the solution treatment can be, but is not limited to, performed in a vacuum heat treatment furnace, and the cooling process can be performed in an inert atmosphere, such as nitrogen.
[0052] In one embodiment of the present application, cryogenic treatment includes treatment at -211°C to -191°C for 50min to 70min. Cryogenic treatment is conducive to producing more martensite and reducing the content of residual austenite. Specifically, the temperature of cryogenic treatment may be, but not limited to, -211°C, -210°C, -205°C, -200°C, -199°C, -196°C, -195°C or -193°C, etc., and the time of cryogenic treatment may be, but not limited to, 50min, 55min, 60min, 65min or 70min, etc. In one embodiment, cryogenic treatment is performed in liquid nitrogen.
[0053] In one embodiment of the present application, the aging treatment includes a treatment at 480°C to 520°C for 3h to 7h, which is conducive to the precipitation and uniform distribution of the dispersed phase, further improving the strengthening effect, and at the same time, a small amount of reverse transformation austenite is generated to improve plasticity. Specifically, the temperature of the aging treatment can be but not limited to 485°C, 490°C, 500°C, 510°C or 515°C, and the time of the aging treatment can be but not limited to 3.5h, 4h, 4.5h, 5h, 5.5h, 6h or 6.5h. In one embodiment of the present application, the aging treatment adopts a staged heating, which can make the aging treatment more stable, the aging effect is better, and it is more conducive to the precipitation of the dispersed phase. In one embodiment, the aging treatment includes a first aging stage and a second aging stage, the temperature of the first aging stage is 150°C to 250°C (such as 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C or 240°C, etc.) and the temperature of the second aging stage is 480°C to 520°C (such as 490°C, 500°C, 510°C or 515°C, etc.). In one embodiment, the holding time of the first aging stage is 20min to 60min (such as 30min, 40min, 50min or 55min, etc.). In one embodiment, the holding time of the second aging stage is 3h to 7h (such as 3.5h, 4h, 5h or 6h, etc.). In one embodiment, the temperature is raised to the first aging stage at a heating rate of 5°C / min to 10°C / min (such as 6°C / min, 7°C / min, 8°C / min or 9°C / min, etc.). In one embodiment, the temperature is raised from the first aging stage to the second aging stage at a heating rate of 8°C / min to 12°C / min (such as 8.5°C / min, 9°C / min, 10°C / min or 11°C / min, etc.). In one embodiment, the aging treatment includes heating to 150°C to 250°C at a heating rate of 5°C / min to 10°C / min and keeping warm for 20min to 60min, and then heating to 480°C to 520°C at a heating rate of 8°C / min to 12°C / min and keeping warm for 3h to 7h, which is conducive to further improving the performance of ultra-high strength steel. In one embodiment, after the aging treatment, the temperature is lowered at a cooling rate of 12°C / min to 18°C / min (such as 13°C / min, 14°C / min, 15°C / min, 16°C / min or 17°C / min, etc.). In one embodiment, nitrogen cooling can be performed after the aging treatment. In one embodiment, the pressure of the aging treatment is less than 0.1kPa.
[0054] See also Figure 2 , is a flow chart of a method for preparing ultra-high strength steel provided in another embodiment of the present application, comprising:
[0055] S201: The iron source, nickel source, cobalt source and molybdenum source are mixed and melted, and then atomized to obtain alloy powder.
[0056] S202: After the alloy powder is mixed with the binder, it is granulated by internal mixing to obtain feed.
[0057] S203: The feed material is injected, degreased and sintered to obtain a prefabricated material.
[0058] S204: Ultra-high strength steel is obtained after heat treatment of prefabricated materials.
[0059] Among them, S202, S203 and S204 refer to the description in the above S101, S102 and S103, which will not be repeated here.
[0060] In S201, according to the content of each element in the ultra-high strength steel, the iron source, nickel source, cobalt source, and molybdenum source are mixed and melted. Among them, a carbon source may be added during the mixing process, or a carbon source may not be added, as long as the carbon element in the ultra-high strength steel is below 0.15wt%. In one embodiment, after the iron source, nickel source, cobalt source, and molybdenum source are mixed, it is necessary to detect the impurity elements therein to ensure that the content of impurity elements in the ultra-high strength steel is within the required range. By mixing and melting the iron source, nickel source, cobalt source, and molybdenum source, each element can be evenly distributed in the alloy powder to ensure the performance of the ultra-high strength steel. In one embodiment, the iron source, nickel source, cobalt source, and molybdenum source can be, but are not limited to, iron element, nickel element, cobalt element, and molybdenum element. In one embodiment, the purity of the iron source, nickel source, cobalt source, and molybdenum source is greater than 99.7%, greater than 99.8%, greater than 99.85%, greater than 99.9%, or greater than 99.99%, etc. In the present application, atomization is carried out under an inert atmosphere to prevent oxygen from oxidizing the alloy. Specifically, the alloy powder can be obtained by water-gas integrated atomization. For example, according to the content of each element in the ultra-high-strength steel, the iron source, nickel source, cobalt source, and molybdenum source are mixed and melted, and the molten metal is poured into an atomizer, first broken into droplets by high-pressure gas, and then formed into alloy powder by high-pressure water flow. The alloy powder is spherical or quasi-spherical. In one embodiment, the particle size D50 of the alloy powder is 7.5μm to 12.5μm, which is conducive to the preparation of feed, and can effectively prevent the excessive volume shrinkage before and after degreasing and sintering from affecting the performance of the final ultra-high-strength steel. Specifically, the particle size D50 of the alloy powder can be, but is not limited to, 7.5 μm, 8 μm, 8.3 μm, 8.5 μm, 8.8 μm, 9 μm, 9.5 μm, 10 μm, 10.5 μm, 11 μm, 12 μm or 12.5 μm. In one embodiment, the particle size D50 of the alloy powder is 8 μm to 10 μm. In another embodiment, the particle size D50 of the alloy powder is 8.5 μm to 10 μm. In yet another embodiment, the particle size D50 of the alloy powder is 8 μm to 8.5 μm.
[0061] The present application also provides an electronic device structural part, the material of which includes the ultra-high strength steel in any of the above embodiments. That is, the electronic device structural part is made of the ultra-high strength steel, so that the electronic device structural part has good strength and plasticity, which is conducive to its application in electronic devices.
[0062] The present application also provides a method for preparing a structural component of an electronic device. Figure 3 , is a flow chart of a method for preparing an electronic device structural component provided in one embodiment of the present application, comprising:
[0063] S301: After the alloy powder is mixed with the binder, it is granulated by internal mixing to obtain feed.
[0064] S302: The feed material is injected, degreased and sintered to obtain a prefabricated part.
[0065] S303: The prefabricated parts are subjected to solution treatment, cryogenic treatment and aging treatment to obtain electronic equipment structural parts. The material of the electronic equipment structural parts includes ultra-high strength steel. The chemical composition of the ultra-high strength steel includes 16wt% to 20wt% Ni, 13wt% to 17.5wt% Co, 5.5wt% to 8.5wt% Mo, less than or equal to 1wt% Cr, less than 2wt% V, less than or equal to 0.35wt% O, less than or equal to 0.15wt% C and the balance Fe.
[0066] Among them, the preparation method of the electronic equipment structural parts can refer to the description of the preparation method of the above-mentioned ultra-high strength steel, which will not be repeated here.
[0067] The preparation method of the electronic device structural part provided by the present application is simple and easy to operate. The structural part of the desired shape can be directly formed without additional mechanical processing. The shape of the structural part is highly variable, and the structural part has excellent strength and plasticity, which is conducive to the application of electronic device structural parts. Specifically, it can be but not limited to preparing miniaturized electronic device structural parts, which helps to reduce weight while maintaining excellent performance, long service life, and low preparation cost.
[0068] In the embodiment of the present application, the surface of the electronic equipment structure can also be treated to further improve its corrosion resistance, wear resistance, oxidation resistance and other properties. In one embodiment, the surface of the electronic equipment structure can be plated to improve the corrosion resistance of the electronic equipment structure, and the appearance of the electronic equipment structure can also be changed by plating. Specifically, the coating can be performed by physical vapor deposition, but not limited to. In another embodiment, the surface of the electronic equipment structure can be passivated to avoid oxygen oxidation of the electronic equipment structure. Specifically, it can be treated with a citrate passivation solution for 120s to 200s at 60°C to 70°C to form a passivation film. In another embodiment, the surface of the electronic equipment structure can be treated with a manganese phosphating treatment to improve its corrosion resistance and wear resistance. Specifically, the manganese phosphating treatment can include pre-treating the electronic equipment structure, then using a manganese phosphating solution for phosphating, baking, sealing, and then drying. In one embodiment, the pretreatment includes washing, deoxidation cleaning (such as potassium hydroxide and or potassium permanganate, etc.), neutralization (such as oxalic acid, etc.), washing, degreasing (such as neutral degreasing agent, etc.), and washing of the electronic equipment structure; surface conditioning treatment can also be performed after the final washing to change the surface microstructure of the electronic equipment structure. In one embodiment, manganese phosphating liquid is used in manganese phosphating treatment, and the manganese phosphating liquid includes manganese salt and phosphate. Among them, the manganese salt can be selected from at least one of manganate, manganese sulfate, and manganese chloride, and the phosphate can be selected from at least one of potassium dihydrogen phosphate and trisodium phosphate. In one embodiment, sealing can be but is not limited to sealing with mineral oil.
[0069] The present application also provides an electronic device, including the above-mentioned electronic device structural parts, which can improve the performance of the electronic device. It can be understood that the electronic device can be but not limited to mobile phones, tablet computers, laptops, watches, MP3, MP4, GPS navigators, digital cameras, etc., and the electronic device structural parts can be but not limited to the housing, middle frame, buttons, shafts (such as slide rails, etc.), hinges, gears, etc. of the electronic device. Please refer to Figure 4, is a front view of an electronic device provided in one embodiment of the present application, the electronic device 400 includes a flexible screen 410 and a foldable mechanism, the foldable mechanism is used to carry the flexible screen 410, and the foldable electronic device can drive the flexible screen 410 to fold or unfold when folded or unfolded; the foldable mechanism includes a hinge assembly 421, a first shell 422 and a second shell 423, the first shell 422, the second shell 423 and the flexible screen 410 are connected and surrounded to form a containing area, and the hinge assembly 421 is arranged in the containing area. In one embodiment, the hinge assembly 421 is an electronic device structural component in any of the above embodiments, thereby improving the reliability and service life of the electronic device 400. In another embodiment, at least one of the first shell 422 and the second shell 423 can be an electronic device structural component in any of the above embodiments, thereby improving the reliability and service life of the electronic device 400.
[0070] The effects of the ultra-high strength steel provided in this application are further illustrated below through specific examples.
[0071] Example 1
[0072] The iron source, nickel source, cobalt source and molybdenum source were mixed and melted in a vacuum environment at 1650°C, and alloy powder was obtained by water vapor atomization. The density of the alloy powder was 8.14 g / cm 3. 90wt% polyoxymethylene, 3wt% antioxidant, 4wt% polyethylene, and 3wt% vinyl acetate polymer were placed in a kneader and mixed at 170°C for 120 minutes to obtain a binder. The binder and alloy powder were mixed in a volume ratio of 2:3 and placed in an internal mixer, mixed at 160°C for 120 minutes to obtain a feed with a melt index of 1450g / 10min. The feed was injected into the mold at an injection temperature of 200°C, an injection pressure of 120MPa, and a cavity temperature of 120°C to form a blank. The blank was placed in nitric acid and nitrogen, heated to 120°C and kept warm for 10 hours for degreasing to remove polyoxymethylene. Then sintering is performed to obtain a prefabricated material, wherein the sintering includes a first stage and a second stage. The first stage is a negative pressure degreasing stage performed in a nitrogen atmosphere with a pressure less than 5kPa, including heating to 380°C for 90 minutes and keeping the temperature for 30 minutes, then heating to 480°C for 60 minutes and keeping the temperature for 120 minutes, then heating to 600°C for 90 minutes and keeping the temperature for 120 minutes. The second stage is a partial pressure sintering stage performed in an argon atmosphere, including heating to 900°C for 120 minutes at a pressure less than 5kPa, adjusting the pressure to 15kPa, keeping the temperature at 900°C for 60 minutes, then heating to 1150°C for 60 minutes and keeping the temperature for 240 minutes, then heating to 1250°C for 100 minutes and keeping the temperature for 240 minutes, finally heating to 1375°C for 135 minutes and keeping the temperature for 240 minutes. After sintering, nitrogen cooling is performed, and the cooling rate is 30°C / min. The prefabricated material is tested and its density is greater than 8g / cm 3 , C content is 0.12wt%, O content is 0.016wt%, and its metallographic diagram is as follows Figure 5 As shown, the scale is 50μm. The figure shows some metallographic sizes, and it can be seen that the average metallographic size is less than 300μm.
[0073] The prefabricated material is placed in a vacuum heat treatment furnace with an air pressure less than -0.1kPa, and the temperature is raised to 200℃ for 30min and kept warm for 30min, then the temperature is raised to 600℃ for 30min and kept warm for 20min at an air pressure less than 0.1kPa, and the temperature is raised to 960℃ for 30min and kept warm for 60min for solution treatment, and then treated in liquid nitrogen at -196℃ for 60min, and then aging treatment is carried out, the air pressure is less than 0.1kPa, and the temperature is raised to 200℃ for 30min and kept warm for 30mi n, the temperature is raised to 500°C for 30 minutes and kept at this temperature for 240 minutes, and then nitrogen is filled in for 30 minutes to cool down, to obtain an ultra-high strength steel material, the ultra-high strength steel comprising 17.5wt% Ni, 14.7wt% Co, 7.4wt% Mo, 0.52wt% Cr, 0.51wt% V, 0.29wt% O, 0.13wt% C, 0.005wt% S, 0.14wt% Si, 0.06wt% Mn and the balance Fe.
[0074] The ultra-high strength steel material is treated with manganese phosphating method for corrosion protection and blackening to produce electronic equipment structural parts with black appearance, such as Figure 6 The electronic equipment components are subjected to a neutral salt spray test. The test conditions are to use a 4.5% to 5.5% sodium chloride aqueous solution with a pH value of 6.5 to 7.2 to spray through a spray device, so that the salt spray settles on the electronic equipment components. After a certain period of time in the test chamber, the surface corrosion state is observed. The temperature of the test chamber is required to be between 33°C and 37°C, the humidity is greater than 95%, and the fogging volume is 1mL / (h·cm 2 ) to 2mL / (h·cm 2 ), nozzle pressure is 78.5kPa to 137.3kPa (0.81.4kgf / cm 2 The neutral salt spray test of this product can last up to 48 hours, which means that there is no obvious change on the surface of the electronic equipment structure after 48 hours of testing.
[0075] Example 2
[0076] The iron source, nickel source, cobalt source and molybdenum source were mixed and melted in a vacuum environment at 1650°C, and alloy powder was obtained by water vapor atomization. The density of the alloy powder was 8.14 g / cm 3. 90wt% polyoxymethylene, 3wt% antioxidant, 4wt% polyethylene, and 3wt% vinyl acetate polymer were placed in a kneader and mixed at 170°C for 120 minutes to obtain a binder. The binder and alloy powder were mixed in a volume ratio of 2:3 and placed in an internal mixer, mixed at 160°C for 120 minutes to obtain a feed with a melt index of 1450g / 10min. The feed was injected into the mold at an injection molding temperature of 200°C, an injection pressure of 120MPa, and a cavity temperature of 110°C to form a blank. The blank was placed in nitric acid and nitrogen, heated to 120°C and kept warm for 10 hours for degreasing to remove polyoxymethylene. Then sintering is carried out to obtain a prefabricated material, wherein the sintering includes a first stage and a second stage. The first stage is a negative pressure degreasing stage carried out in a nitrogen atmosphere with a pressure less than 5 kPa, including heating to 380°C for 90 minutes and keeping warm for 30 minutes, heating to 480°C for 60 minutes and keeping warm for 120 minutes, and then heating to 600°C for 90 minutes and keeping warm for 120 minutes. The second stage is a partial pressure sintering stage carried out in an argon atmosphere, including heating to 900°C for 120 minutes at a pressure less than 5 kPa, adjusting the pressure to 15 kPa, keeping warm at 900°C for 60 minutes, heating to 1150°C for 60 minutes and keeping warm for 240 minutes, then heating to 1250°C for 100 minutes and keeping warm for 240 minutes, and finally heating to 1385°C for 135 minutes and keeping warm for 240 minutes. Nitrogen cooling is carried out after sintering, and the cooling rate is 30°C / min. The prefabricated material was tested and its density was greater than 8.05g / cm 3 , C content is 0.08wt%, O content is 0.011wt%, and its metallographic diagram is as follows Figure 7 As shown, the scale is 100μm. The figure shows some metallographic sizes. It can be seen that the average size of the metallographic structure is less than 300μm.
[0077] The prefabricated material is placed in a vacuum heat treatment furnace with an air pressure less than -0.1kPa, and the temperature is raised to 200℃ for 30min and kept warm for 30min. The temperature is raised to 600℃ for 30min and kept warm for 20min under an air pressure less than 0.1kPa, and the temperature is raised to 960℃ for 30min and kept warm for 60min for solution treatment, and then treated in liquid nitrogen at -196℃ for 60min, and then aging treatment is performed with an air pressure less than 0.1kPa, and the temperature is raised to 200℃ for 30min and kept warm for 30min , the temperature is raised to 500°C for 30 minutes and kept at this temperature for 240 minutes, and then nitrogen is filled in for 30 minutes to cool down, to obtain an ultra-high strength steel material, the ultra-high strength steel comprising 17.1wt% Ni, 15.5wt% Co, 7.8wt% Mo, 0.54wt% Cr, 0.48wt% V, 0.31wt% O, 0.13wt% C, 0.003wt% S, 0.11wt% Si, 0.02wt% Mn and the balance Fe.
[0078] A nickel-phosphorus alloy (3μm to 5μm thick) is formed on the surface of ultra-high-strength steel material by water plating, and then chrome is plated by physical vapor deposition to obtain a product with a dark tan appearance. The neutral salt spray test can last up to 48 hours.
[0079] Embodiment 3-8
[0080] The difference between Examples 3-8 and Example 1 is that the contents of various elements in the ultra-high strength steel are different, as shown in Table 1, wherein the contents of P, Ti and Al in the ultra-high strength steels prepared in Examples 1-8 are all less than 0.01wt%, and are not shown in Table 1.
[0081] Table 1 Content of each element in the ultra-high strength steel obtained in Examples 1-8
[0082]
[0083]
[0084] Comparative Examples 1-7
[0085] The difference between Comparative Examples 1-7 and Example 1 is that the contents of the elements in the steel are different, as shown in Table 2.
[0086] Table 2 Content of each element in the steel obtained in Comparative Examples 1-7
[0087] Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Comparative Example 7 Ni(wt%) 14 22 18.2 17.8 19.2 17.3 18.9 Co(wt%) 15.1 16.2 12.5 18 16.3 16.8 14.8 Mo (wt%) 6.2 6.4 6.2 7.1 5 9 6.3 Cr(wt%) 0.71 0.61 0.63 0.78 0.62 0.73 0.51 V(wt%) 0.61 0.58 0.62 0.59 0.71 0.58 0.64 C (wt%) 0.14 0.13 0.13 0.14 0.16 0.11 0.2 O(wt%) 0.33 0.21 0.28 0.26 0.32 0.33 0.27 S (wt%) 0.004 0.007 0.006 0.008 0.004 0.009 0.006 Si (wt%) 0.010 0.012 0.12 0.13 0.14 0.13 0.15 Fe(wt%) margin margin margin margin margin margin margin
[0088] The ultra-high strength steels prepared in Examples 1-8 and the steels prepared in Comparative Examples 1-7 were subjected to performance tests, and the results are shown in Table 3, wherein the yield strength, tensile strength, elongation and elastic modulus were tested according to GB / T 228.1-2021.
[0089] Table 3 Performance test results
[0090] Yield strength(MPa) Tensile strength(MPa) Elongation(%) Elastic modulus(Gpa) Example 1 2104.25 2245.4 5.4 185.05 Example 2 2210 2352.4 4.4 190.1 Example 3 2226 2398 4.2 185.2 Example 4 2198 2302 5.6 182.9 Example 5 2021 2132 5.1 178.3 Example 6 2158 2278 5.4 182.7 Example 7 2270 2402 4.1 183.1 Example 8 2277 2451 4.0 192.2 Comparative Example 1 1878 1985 3.5 178.3 Comparative Example 2 1911 2021 3.9 180.2 Comparative Example 3 1811 1951 4.3 175.8 Comparative Example 4 2011 2121 2.8 181.2 Comparative Example 5 1859 2014 3.6 189.3 Comparative Example 6 2017 2178 1.5 187.9 Comparative Example 7 1898 1968 4.1 178.9
[0091] It can be seen that the yield strength and tensile strength of the ultra-high strength steels obtained in Examples 1-3, 5, and 7 are low, and cannot meet the use requirements of high yield strength and high tensile strength; although the ultra-high strength steels obtained in Examples 4 and 6 have slightly higher yield strength and tensile strength, their elongation is too low and cannot meet the use requirements. The ultra-high strength steels obtained in Examples 1-8 of the present application have both high yield strength and tensile strength, and good elongation and elastic modulus, excellent comprehensive performance, and can better meet the use requirements, which is conducive to use in electronic equipment; at the same time, Figure 6 As shown, the preparation method provided in the present application can be used to design the shape of ultra-high strength steel while preparing it, so that a product of a desired shape can be obtained while obtaining ultra-high strength steel, reducing CNC and other mechanical processing processes, which is more conducive to its widespread use.
[0092] The above is a detailed introduction to the contents provided in the implementation mode of the present application. This article explains and illustrates the principles and implementation modes of the present application. The above explanation is only used to help understand the method and core idea of the present application. At the same time, for those skilled in the art, according to the idea of the present application, there will be changes in the specific implementation mode and application scope. In summary, the contents of this specification should not be understood as limiting the present application.
Claims
1. An ultra-high strength steel, It is characterized in that The chemical composition of the ultra-high strength steel includes 16wt% to 20wt% Ni, 13wt% to 17.5wt% Co, 5.5wt% to 8.5wt% Mo, less than or equal to 1wt% Cr, less than 2wt% V, less than or equal to 0.35wt% O, less than or equal to 0.15wt% C, and the balance Fe.
2. The ultra-high strength steel according to claim 1, It is characterized in that The content of Ni in the ultra-high strength steel is 16 wt % to 18 wt %.
3. The ultra-high strength steel according to claim 1, It is characterized in that The content of Co in the ultra-high strength steel is 13.5wt% to 17.5wt%.
4. The ultra-high strength steel according to claim 1, It is characterized in that The content of Mo in the ultra-high strength steel is 6wt% to 7.4wt%.
5. The ultra-high strength steel according to claim 1, It is characterized in that The ultra-high strength steel further includes impurity elements, The content of the impurity elements in the ultra-high strength steel is less than or equal to 0.5 wt %.
6. The ultra-high strength steel according to claim 1, It is characterized in that The impurity element includes at least one of S, Si, Mn, P, Ti and Al; The content of S in the ultra-high strength steel is less than or equal to 0.02wt%; The content of Si in the ultra-high strength steel is less than or equal to 0.2wt%; The content of Mn in the ultra-high strength steel is less than or equal to 0.1wt%; The content of P in the ultra-high strength steel is less than or equal to 0.01wt%; The content of Ti in the ultra-high strength steel is less than or equal to 0.01wt%; The content of Al in the ultra-high strength steel is less than or equal to 0.01 wt %.
7. The ultra-high strength steel according to claim 1, It is characterized in that The yield strength of the ultra-high strength steel is greater than or equal to 2000 MPa, the tensile strength is greater than or equal to 2100 MPa, the elongation is greater than or equal to 3%, and the elastic modulus is greater than or equal to 170 Gpa.
8. The ultra-high strength steel according to claim 7, It is characterized in that The ultra-high strength steel has a yield strength of 2000 MPa to 2250 MPa, a tensile strength of 2100 MPa to 2450 MPa, an elongation of 3% to 6%, and an elastic modulus of 170 Gpa to 195 Gpa.
9. A method for preparing ultra-high strength steel, It is characterized in that include: After the alloy powder is mixed with the binder, it is granulated by internal mixing to obtain the feed material; The feed material is injected, degreased and sintered to obtain a prefabricated material; The prefabricated material is subjected to heat treatment to obtain ultra-high strength steel, wherein the chemical composition of the ultra-high strength steel includes 16wt% to 20wt% of Ni, 13wt% to 17.5wt% of Co, 5.5wt% to 8.5wt% of Mo, less than or equal to 1wt% of Cr, less than 2wt% of V, less than or equal to 0.35wt% of O, less than or equal to 0.15wt% of C, and the balance of Fe.
10. The preparation method according to claim 9, It is characterized in that The sintering includes a first stage and a second stage, wherein the first stage includes keeping the temperature at 350° C. to 610° C. for 4 to 8 hours, and the second stage includes keeping the temperature at 1140° C. to 1385° C. for 8 to 18 hours.
11. The preparation method according to claim 10, It is characterized in that The first stage includes heating to 350°C to 400°C at a heating rate of 2°C / min to 5°C / min and keeping the temperature for 20min to 40min, then heating to 450°C to 500°C at a heating rate of 1°C / min to 3°C / min and keeping the temperature for 100min to 150min, then heating to 580°C to 610°C at a heating rate of 1°C / min to 3°C / min and keeping the temperature for 100min to 150min, the first stage is carried out under negative pressure, and the negative pressure is less than 5kPa; The second stage comprises heating from the first stage to 900°C to 950°C at a heating rate of 2°C / min to 3°C / min and keeping the temperature for 50min to 70min, then heating to 1130°C to 1160°C at a heating rate of 3°C / min to 5°C / min and keeping the temperature for 200min to 250min, then heating to 1230°C to 1260°C at a heating rate of 0.8°C / min to 1.2°C / min and keeping the temperature for 200min to 250min, and finally heating to 1350°C to 1390°C at a heating rate of 0.8°C / min to 1.2°C / min and keeping the temperature for 200min to 250min; After the sintering, the temperature is cooled at a cooling rate of 35°C / min to 45°C / min.
12. The preparation method according to claim 9, It is characterized in that The heat treatment includes sequentially performing solution treatment, cryogenic treatment and aging treatment; The solution treatment comprises treating at 940° C. to 970° C. for 45 min to 70 min; The cryogenic treatment includes treating at -211°C to -191°C for 50min to 70min; The aging treatment includes treating at 480° C. to 520° C. for 3 h to 7 h.
13. The preparation method according to claim 12, It is characterized in that The solution treatment includes heating to 180°C to 220°C at a heating rate of 4°C / min to 7°C / min and keeping the temperature for 20min to 45min, then heating to 580°C to 620°C at a heating rate of 8°C / min to 12°C / min and keeping the temperature for 15min to 30min, and then heating to 940°C to 970°C at a heating rate of 10°C / min to 15°C / min and keeping the temperature for 45min to 70min; The aging treatment includes heating to 150°C to 250°C at a heating rate of 5°C / min to 10°C / min and keeping the temperature for 20min to 60min, and then heating to 480°C to 520°C at a heating rate of 8°C / min to 12°C / min and keeping the temperature for 3h to 7h; After the aging treatment, the temperature is cooled at a cooling rate of 12°C / min to 18°C / min.
14. An electronic equipment structural part, It is characterized in that The material of the electronic equipment structural component includes the ultra-high strength steel described in any one of claims 1 to 8 or the ultra-high strength steel prepared by the preparation method described in any one of claims 9 to 13.
15. An electronic device, It is characterized in that The electronic device structural component comprises the electronic device structural component as claimed in claim 14.
